Genotypic differences in response to Hygromycin effect on untransformed calli death and rice germination (Bangladesh Rice Journal, 2015)
Hygromycin is an efficient selective agent in transformation studies of wide ranges of crop. In this study, different concentrations of hygromycin were used to observe the effect on untransformed calli death, percent germination and seedling growth of three rice varieties (Oryza sativa L.) viz BRRI dhan29, MR219 and Taipei309. Hygromycin killed the untransformed calli and inhibited the germination of tested varieties in a concentration dependent manner. Among the tested varieties, the lowest and the highest calli death was observed in MR219 and Taipei309 respectively in all the concentrations of hygromycin. Whereas, the highest and the lowest percent germination were observed in MR219 and Taipei309 respectively. The minimal inhibitory concentration (MIC) for selection of calli were calculated as 42, 40 and 47 mg/L hygromycin for BRRI dhan29, MR219 and Taipei309 respectively. During germination, 35, 62 and 32 mg/L hygromycin were suitable for the selection of BRRI dhan29, MR219 and Taipei 309 respectively. Shoot and root growth reduction after germination was increased with the increased concentration of hygromycin. Besides, root growth was more sensitive to hygromycin than the shoot. These results suggest that hygromycin increases calli death, decreases percent germination, and shoot and root growth in all varieties with the increasing rate of hygromycin. But these characteristics vary with different degrees in different genotypes as well as different stages.Bangladesh Rice j. 2014, 18(1&2): 38-43